Psychometric equivalence of electronic and telephone completion of the ICIQ modules. Issue 5 (11th August 2016) - Uren, Alan D.; Cotterill, Nikki; Parke, Sophie E.; Abrams, Paul
Abstract : Aims: To assess the equivalence of touch‐screen (hand‐held iPad) and telephone completion of patient‐completed International Consultation on Incontinence Questionnaire (ICIQ) modules by comparison with corresponding data collected using conventional paper‐and‐pencil methods. Methods: Men and women, attending urology outpatients complaining of LUTS, were randomised to one of three groups which determined the order in which they completed three administrations of the same questionnaire: paper, iPad and telephone. Four ICIQ questionnaires were evaluated: ICIQ‐MLUTS, ICIQ‐LUTSqol, ICIQ‐OABqol and ICIQ‐UI SF. Results: From August 2012 to October 2014 a total of 448 out of 491 (91%) recruits completed the first two administrations and were included in the analysis. Three hundred forty‐eight out of 491 (71%) completed the phone administration. The intra‐class correlation coefficient (ICC) and Kappa statistic were calculated where appropriate between completed pairs of administrations. Mean ICC correlations were high (>0.8) between paper and iPad administrations. Paired paper and phone administrations were less well correlated, although still high (mean ICC>0.75). This may be partly due to the practical limitation that the phone interview was completed up to a week later than the initial two administrations. There was no evidence that potential moderator effects (gender, age and experience with computers or touch screen devices) significantly affected overall reliability of scores between administrations. Conclusions: We can recommend the interchangeable use of ICIQ electronic or paper based questionnaires in a clinical or research setting. Self‐report is preferable to telephone delivery where possible. Neurourol. Urodynam. 9999:XX–XX, 2016 . © 2016 Wiley Periodicals, Inc.